Development of Science Teaching Materials Based on Ecological Value of Mangrove Ecosystems as a Strategy to Improve Science Literacy of Junior High School Students on the South Coast of East Lombok - Didik Santoso; Abdul Syukur; Lalu Zulkifli; Zulhalifah Zulhalifah (Postgraduate, University of Mataram, 2022)
Environmental characteristics in coastal areas receive less attention from educational aspects, especially schools integrating with science learning. This research aims to develop mangrove ecological value-based teaching materials as a strategy to improve students' science literacy. The research methods used are observation methods and quasi-experiments. Data analysis uses descriptive statistical analysis using, then the normality and homogeneity test is done with SPSS 17.0. Next, to test the hypothesis using ANOVA One Way. The science literacy ability of learners is measured using pre-test and post-test questionnaires. The results showed that mangrove ecological value-based teaching materials are worth using based on expert and teacher validation. The response of learners to the teaching materials developed is very interesting. The homogeneity test showed the significance of students' science literacy abilities obtained Levene test scores > 0.05 which means the data is homogeneous. Based on the hypothesis test H0 was rejected, which means there is a significant increase in student science literacy after using teaching materials based on the ecological value of mangrove ecosystems. The effectiveness of teaching materials is evidenced by the percentage of changes in learners' average pre-test and post-test results. The highest post-test grade post-test score was 80.35%, and the lowest was 79.44%. The conclusion is that mangrove ecological value-based teaching materials are significant to students’ science literacy skills, especially in the coastal areas of East Lombok. Therefore, it is necessary to utilize the location's potential as a source of learning learners to be more attractive.